How students understand smaller fractions divided by greater fractions? - Kamirsyah Wahyu (Beta: Jurnal Tadris Matematika, 2021)
This paper discusses how 5th-grade students understand quotative fractions division or smaller fractions divided by greater fractions in specific. A context-based mathematics task, making posters, was developed and implemented in two Realistic Mathematics Education (RME)-based lessons involving 6 students and 28 students. The analysis of students’ group discussion and works on the task reveal that the students initially experienced difficulties in determining how many posters can be made using 1/2 of one paper if one poster requires 3/4 of a paper. To support students’ understanding, a task, which carefully sequences fractions division content and utilizes contexts that can be easily modeled, is required.